Penggunaan Trichoderma sp.dan Penyambungan untuk Mengendalikan Penyakit Utama Tanaman Tomat (Licopersicum esculentum Mill.) di Desa Bangli, Kecamatan Baturiti, Tabanan - I PUTU BAWA ARIYANTA; I PUTU SUDIARTA; DWI WIDANINGSIH; I KETUT SUMIARTHA; GUSTI ALIT SUSANTA WIRYA; MADE SUPARTHA UTAMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Utilization of Trichoderma sp. and Grafting to Controlthe Mayor Diseases of Tomato (Licopersicum esculentum Mill.) in Bangli Village, Baturiti, Tabanan Control of plant diseases is one of the constraints in the cultivation of tomatoes. Control method performed by farmers generally use synthetic pesticides, however that cause environmental pollution. The use of Trichoderma sp. and grafting is an environmentally friendly technology in controlling plant diseases. The purpose of this study was in order to determine the ability of Trichoderma sp. and the grafting between the eggplant EG203 strain as rootstock and scions tomatoes as to control major diseases and improve tomato production. This study used a factorial randomized block design with six treatments and four replications.Diseases were found in field tomatoes are late blight (Phytophthora infestans) and yellow curly leaf disease (Tomato Yellow Leaf Curl Virus). Statistical analysis showed that Trichoderma sp. and grafting can reduce the disease severity of leaf blight and increase the production of tomato plants, but was unable to control the disease yellow leaf curl. Average of disease severity of leaf blight on grafting with screen and Trichoderma sp. was lower (61.11 and 62.03%) when compared to treatment without grafting and without Trichoderma sp. (82.99 and 75.47%). Average of yields on treatment grafting with screen and Trichoderma sp. was higher (3912.50 and 3822.22 g/plant) compared to treatment without grafting and without Trichoderma sp. (2858.33 and 3280.55 g/plant). Keywords: disease of tomato, Trichoderma sp., and grafting.